Mucoadhesive gel containing immunotherapeutic nanoparticulate satranidazole for treatment of periodontitis: Development and its clinical implications - Singh Y.; Vuddanda P.R.; Jain A.; Parihar S.; Chaturvedi T.P.; Singh S. (My University, 2025)
The aim of this study was to alleviate shortcomings in periodontal treatment by utilizing a mucoadhesive gel containing immunotherapeutic ganglioside coated polymeric nanoparticles (G-PNP) bearing satranidazole (SZ). Nanoprecipitation was used to fabricate SZ loaded G-PNP. In our previous deliberations aqueous dispersibility of conventional SZ had raised dose consistency issues. Usage of G-PNP allayed those fears as DSC and XRD data showed that SZ was rendered amorphous (more water dispersible than crystalline SZ) when captured in a polymeric matrix of nanoparticles. G-PNP were added to sodium carboxy methyl cellulose (SCMC 30 NP) gels and compared against SCMC 30 (gel containing conventional SZ) for texture, mucoadhesion, drug release and inhibitory susceptibility of Aggregatibacter actinomycetomicans. Subsequently a 21 day single blind clinical trial comparing the efficacy of SCMC 30 NP and SCMC 30 was conducted. SCMC 30 NP showed a maximum mucoadhesion force (43.27 ± 4.10 gf), low hardness (12.28 ± 0.17 N), moderate gel strength (8.53 ± 0.21 N) and elasticity (5.50 ± 0.03 mm). 'Well' diffusion data revealed qualitatively greater antibacterial activity of SCMC 30 NP. Dissolution studies demonstrated diffusion controlled release of SZ at concentrations above MIC. SCMC 30 NP caused a significant (P < 0.05) decrease in clinical markers of periodontitis, i.e. gingival index and pocket depth as compared to SCMC 30. Also reduction in the plaque index produced by SCMC 30 NP was highly significant (P < 0.01) as compared to SCMC 30 at the end of the 21st day of clinical study. Amelioration of disease was improved due to Th-2 biased immuno shifting mediated by G-PNPs, which increased secretion of anti-inflammatory cytokines like IL-4 and TGF-β from J774 macrophages. Clinical benefits incurred along with ease of application calls for a scaled up investigation of SCMC 30 NP. © The Royal Society of Chemistry 2015.